Depression in HIV Positives under ART in TUTH Clinic: A Cross-Sectional Study - Tiwari, S.; Ojha, S.P.; Chapagai, M.; Tulachan, P.; Dhungana, S. (Journal of Psychiatrists' Association of Nepal, 2017)
Introduction: Among PLWHA, most studies have reported a high prevalence (20-37%) of depression, which negatively impacts the adherence to ART, and leads to increased morbidity and mortality. Objective: This study aims to study depression among PLWHA who were under ART in the out-patient HIV clinic Method: This study was conducted at the outpatient HIV clinic in a tertiary center (TUTH). All relevant information were noted in a semistructured proforma designed for the study. BDI-II and ICD-10 DCR were the tools used. Result: Out of total 99 patients, 34 were depressed (34.2%), moderate depression with somatic syndrome category being the majority (19, 19.2%) (p< 0.05). Depression was significantly associated with low family income, alcohol use and past history of depression. Conclusion: Depression was found to be highly prevalent in PLWHA who were under ART